Anatomical and physiological characteristics of claustrum neurons in primates and rodents - Chong, Melissa H. Y.; Gămănuţ, Răzvan (Frontiers in Mammal Science, 2024)
The claustrum, a structure having extensive connectivity with the rest of the brain and being involved in many high-cognitive processes, is still one of the least understood parts of the mammalian nervous system. Accelerated advancement of genetic tools for rodents in the last decade have resulted in many breakthroughs about its interaction with cortical and subcortical regions, while human/primate studies have been invaluable in revealing its effects on conscious behaviour. However, these findings did not elucidate conclusively the principles of its internal dynamics, which would clarify its function within the brain network. The first step in this direction is to know the characteristics of major types of neurons in the claustrum. In this review, we are looking at the data allowing a comparison between the main neuronal types of the claustrum in primates and rodents, with the aim of showing the extent of known commonalities and differences, and highlighting the research gap between the two orders. The results indicate that in both there is a ratio excitatory/inhibitory neurons higher than in the cortex, but with a lower baseline activity of the excitatory neurons due to the higher inhibition. The local excitation in the claustrum is provided by collaterals of neurons projecting to the cortex. Secondary neuronal markers such as Calcium binding proteins and somatostatin tend to be expressed differently in the claustrum of primates than in that of rodents, specifically in more classes of neurons and across a larger area. The spatial distribution of neuropeptide Y might be a conserved motif across the two orders. The work in rodents has an undisputable advance in the study of electrical properties for each class of claustrum neurons. However, for a deep understanding of the claustrum function in the human brain, primate studies remain indispensable.